2022
DOI: 10.3389/fnmol.2021.819440
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Type Glycogen Phosphorylase Is Crucial for Astrocytic Glycogen Accumulation in Chronic Social Defeat Stress-Induced Depression in Mice

Abstract: Astrocytic glycogen plays an important role in brain energy metabolism. However, the contribution of glycogen metabolism to stress-induced depression remains unclear. Chronic social defeat stress was used to induce depression-like behaviors in mice, assessed with behavioral tests. Glycogen concentration in the medial prefrontal cortex (mPFC) and the expression of key enzymes of the glycogen metabolism were investigated using Western blots, immunofluorescent staining, electron microscopy, and biochemical assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Advancement in molecular research revealed that social defeat stress specifically increases c-Fos expression (a marker for neuronal activity) in the PFC ( Numa et al, 2019 ), and social stress-induced behavioral deficits are mediated by molecular adaptations in the prefrontal cortical circuit involving ΔFosB and cholecystokinin ( Vialou et al, 2014 ). Besides, dopamine D2 receptor dimerization ( Bagalkot et al, 2015 ) and astrocytic glycogen accumulation ( Zhu et al, 2021 ) in PFC is also closely related to stress-induced depression-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Advancement in molecular research revealed that social defeat stress specifically increases c-Fos expression (a marker for neuronal activity) in the PFC ( Numa et al, 2019 ), and social stress-induced behavioral deficits are mediated by molecular adaptations in the prefrontal cortical circuit involving ΔFosB and cholecystokinin ( Vialou et al, 2014 ). Besides, dopamine D2 receptor dimerization ( Bagalkot et al, 2015 ) and astrocytic glycogen accumulation ( Zhu et al, 2021 ) in PFC is also closely related to stress-induced depression-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of PYGB leads to the dysfunction of glycogen decomposition and, thus, glycogen storage. PYGB contributes to stress-induced depression-like behaviors and is a promising therapeutic target for the treatment of depression [105].…”
Section: Pygb In Depressionmentioning
confidence: 99%
“…While the GPh activity assay is well-established using high performance liquid chromatography (4,5), these enzyme assays with commercially available alternatives have low sensitivity, are complex and lack versatility in their application. While the assay is well-established for liver and brain tissue (5)(6)(7), its applicability to muscle, another significant site of glycogen storage, has been less explored.…”
Section: Introductionmentioning
confidence: 99%